The tadpole of Bokermannohyla capra Napoli & Pimenta 2009 (Anura, Hylidae) - de Almeida Mercês, Ednei; Protázio, Airan Dos Santos; Juncá, Flora Acuña (Zootaxa, 2012)
Bokermannohyla capra is a member of the clade B. circumdata group (Faivovich et al. 2005) that contains 18 nominal species from the Atlantic Rainforest (Napoli & Pimenta 2009). We describe herein the previously unknown tadpole of B. capra and compare it with tadpoles of other species of the group.